Physical activity maintenance among young adult cancer survivors in an mHealth intervention: Twelve‐month outcomes from the IMPACT randomized controlled trial - Carmina G. Valle; Molly A. Diamond; Hillary M. Heiling; Allison M. Deal; Derek P. Hales; Brooke T. Nezami; Jessica Gokee LaRose; Christine M. Rini; Bernardine M. Pinto; Deborah F. Tate (Cancer Medicine, 2023)
Abstract Background Most physical activity (PA) interventions in young adult cancer survivors (YACS) have focused on short‐term outcomes without evaluating longer‐term outcomes and PA maintenance. This study examined the effects of an mHealth PA intervention at 12 months, after 6 months of tapered contacts, relative to a self‐help group among 280 YACS. Methods YACS participated in a 12‐month randomized trial that compared self‐help and intervention groups. All participants received an activity tracker, smart scale, individual videochat session, and access to a condition‐specific Facebook group. Intervention participants also received lessons, tailored feedback, adaptive goal setting, text messages, and Facebook prompts for 6 months, followed by tapered contacts. Accelerometer‐measured and self‐reported PA (total [primary outcome], moderate‐to‐vigorous [MVPA], light, steps, sedentary behaviors) were collected at baseline, 6, and 12 months. Generalized estimating equation analyses evaluated group effects on outcomes from baseline to 12 months. Results From baseline to 12 months, there were no between‐ or within‐group differences in accelerometer‐measured total PA min/week, while increases in self‐reported total PA were greater in the intervention versus self‐help group (mean difference = +55.8 min/week [95% CI, 6.0–105.6], p = 0.028). Over 12 months, both groups increased accelerometer‐measured MVPA (intervention: +22.5 min/week [95% CI, 8.8–36.2] vs. self‐help: +13.9 min/week [95% CI, 3.0–24.9]; p = 0.34), with no between‐group differences. Both groups maintained accelerometer‐measured and self‐reported PA (total, MVPA) from 6 to 12 months. At 12 months, more intervention participants reported meeting national PA guidelines than self‐help participants (47.9% vs. 33.1%, RR = 1.45, p = 0.02). Conclusion The intervention was not more effective than the self‐help group at increasing accelerometer‐measured total PA over 12 months. Both groups maintained PA from 6 to 12 months. Digital approaches have potential for promoting sustained PA participation in YACS, but additional research is needed to identify what strategies work for whom, and under what conditions.